VIOLENCE AND THE URBAN ENVIRONMENT: AN ECOCRITICAL READING OF MORIRÁS LEJOS BY JOSÉ EMILIO PACHECO. - Lee, Diana Dodson (Chasqui (01458973), 2019)
A literary criticism for the book "Morirás lejos" by José Emilio Pacheco, is presented. Topics discussed include postmodern emphasis on historical metafiction in Pacheco's novel; novel demonstrates an intricate and dynamic relationship between violence and nature; degradation of the natural environment in the urban spaces in the book.